2003
DOI: 10.1002/jgm.392
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral VEGF‐A gene transfer induces angiogenesis and promotes bone formation in healing osseous tissues

Abstract: Our data confirm the important role of VEGF in bone healing. We show for the first time that adenoviral VEGF-A gene transfer may modify bone defect healing in a rodent model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(97 citation statements)
references
References 41 publications
6
90
1
Order By: Relevance
“…1,2 Efforts to enhance fracture neovascularization by supplementing with recognized proangiogenic cytokines have yielded promising results. [3][4][5][6]39 However, the resident population of endothelial cells that is responsive to available levels of angiogenic growth factors may potentially limit the extent to which supplementation enhances tissue neovascularization. Situations which classically exhibit compromised endothelial function and angiogenesis are well recognized in contributing to the significant complications of delayed fracture healing and atrophic non-union.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Efforts to enhance fracture neovascularization by supplementing with recognized proangiogenic cytokines have yielded promising results. [3][4][5][6]39 However, the resident population of endothelial cells that is responsive to available levels of angiogenic growth factors may potentially limit the extent to which supplementation enhances tissue neovascularization. Situations which classically exhibit compromised endothelial function and angiogenesis are well recognized in contributing to the significant complications of delayed fracture healing and atrophic non-union.…”
Section: Introductionmentioning
confidence: 99%
“…The function of cellular localization also plays an important role for the transfer of bone marrow cells to fracture callus (Devine et al, 2002). In vivo experiments demonstrated that the pluripotent bone marrow cells containing many fracture repair cellular elements need to be transferred to the fracture callus (Devine et al, 2002;Tarkka et al, 2003). In the plate fixation group, most of the enriched functions were similar to those of the nail fixation group.…”
Section: Discussionmentioning
confidence: 99%
“…Extrinsic or host-driven vascularization can be stimulated through local administration of VEGF (Takeshita et al, 1994). As it is the main angiogenic growth factor in fracture healing, VEGF has been shown to enhance bone regeneration (Street et al, 2002;Tarkka et al, 2003). However, safety concerns exist over the use of high-dosed VEGF (Lee et al, 2000;Maes et al, 2010;Vajanto et al, 2002), which may lead to fibrosis and abnormal blood vessel formation and function.…”
Section: Reducing Hypoxia Through Extrinsic Angiogenesismentioning
confidence: 99%